P07.24 Predicted inclusivity and specificity of the cobas® 4800 ct/ng test through global surveillance monitoring. (13th September 2015) - Hibbard, S Cayabyab; Chen, X; Osiecki, J; Honisch, C; Lewinski, M; Fillmore, C
Abstract : Introduction: Nucleic acid amplification tests rely on conserved sequences for identification of specific targets, which may evolve, requiring global surveillance monitoring. An analysis of sequence heterogeneity within the primer and probe target region for the cobas ® 4800 CT/NG Test was performed with publically available and in-house sequences to determine predicted inclusivity and specificity. Methods: To determine predicted inclusivity, analysis of the sequence heterogeneity within the primer and probe binding regions used in cobas ® 4800 CT/NG Test were compared with the most current sequence information in NCBI's public sequence database supplemented with sequences generated by the Roche Global Surveillance Program. By design of the redundant nature of target amplification and detection for these assays (multiple copies of DR9 in NG and dual targets of omp A and cryptic plasmid in CT), mismatches in multiple sequences are required to affect assay inclusivity. For predicted specificity, the analysis of the potential generation of false-positive signals due to detection of non-target sequences was evaluated by interrogating the most current sequence information in NCBI's public sequence database. Results: For predicted inclusivity, a total of 56 cryptic plasmid and 373 omp A sequences from Chlamydia trachomatis and 357 sequences from 119 different strains of Neisseria gonorrhoeae covering the primer/probe binding region showed no predicted critical mismatches. For predicted specificity, extensive search identified no non- CT or NG target sequences that fit the broad criteria for potentially generating a false-positive signal based on the binding of two primers in the proper orientation, having a sequence that may bind one of the probes and generating a signal for an amplicon size of less than 3, 000 base pairs. Conclusion: Global surveillance of publically available and in-house generated sequences shows the cobas ® 4800 CT/NG Test is a reliable molecular method for detection of Chlamydia trachomatis and Neisseria gonorrhoeae, displaying excellent predicted inclusivity and specificity. Disclosure of interest: The authors are employees of Roche Molecular Diagnostics which supported this study.